(untitled) (Research, Society and Development, 2020)
The objective of the experiment to study the time intervals and the number of days of observation to assess the feeding behavior of feedlot lambs. We used 25 steers average weight of 23,80 ± 2,0 kg. The animals were housed in individual stalls and randomly assigned to five diets consisting of roughage (hay tifton) and concentrates from corn, soybeans and glycerol levels, provided in a 60:40 ratio (FCR) twice a day. The record of the activities was conducted during three periods of 24 hours, recording the time spent eating, rumination and making up the discretization of these series in number of feeding period, ruminating and resting, and efficiencies of feeding and rumination dry matter and neutral detergent fiber. Treatments consisted of: 0, 3, 6, 9 and 12% glycerol instead of dry matter in corn diet, and had five replicates per treatment. The time spent eating, ruminating and resting period and the number of rumination did not differ in any level of glycerol in the diet. However, the number of feeding periods and idle, showed significant differences. We conclude that the addition of glycerol in diets for feedlot lambs in partial substitution of corn, did not affect the time spent eating, ruminating and leisure, the number of rumination period. However, it can affect the number of feeding period and idleness.